1989
DOI: 10.2105/ajph.79.6.770
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported diabetes in Mexican Americans: HHANES 1982-84.

Abstract: In the Hispanic Health and Nutrition Examination Survey (HHANES) of 3,928 Mexican Americans ages 20-74 years, the age-adjusted prevalence of self-reported diabetes was 6.8 percent among men and 7.6 percent among women. Comparable age-adjusted rates for the US population in a national survey were 2.9 percent in men and 3.8 percent in women. The prevalence of diabetes in Mexican Americans is greater in older age groups, was similar in men and women, and among women only was inversely associated with education. (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…We were able to document that 80% of the Bell's palsy patients classified as diabet ic in our study were currently prescribed eith er insulin therapy or oral medications. The proportion of Bell's palsy cases reporting con trol o f diabetes by diet alone (12%) was simi lar to that observed among self-reported dia betes in the H H A N E S [58]. While acknowl edging that reliance upon limited medical his tories may have led to some underascertain ment of diabetes in the study population, we believe that the ascertainment o f diabetes was of nearly equivalent quality in the population comparisons, and that the standardized prev alence ratios for diabetes are only minimally biased in our study.…”
Section: Limitationsmentioning
confidence: 55%
See 1 more Smart Citation
“…We were able to document that 80% of the Bell's palsy patients classified as diabet ic in our study were currently prescribed eith er insulin therapy or oral medications. The proportion of Bell's palsy cases reporting con trol o f diabetes by diet alone (12%) was simi lar to that observed among self-reported dia betes in the H H A N E S [58]. While acknowl edging that reliance upon limited medical his tories may have led to some underascertain ment of diabetes in the study population, we believe that the ascertainment o f diabetes was of nearly equivalent quality in the population comparisons, and that the standardized prev alence ratios for diabetes are only minimally biased in our study.…”
Section: Limitationsmentioning
confidence: 55%
“…Data from the H H A N E S indicate that the prevalence of self-reported diabetes among Mexican-Amer icans is 2-to 3-fold greater than among the general U S population [58], and these selfreported rates are substantiated by communi ty studies using laboratory methods. In addi tion to increased mortality, serious complica tions of diabetes, e.g., end stage renal disease [60] and proliferative diabetic retinopathy [61,62] are common among Mexican-Ameri cans.…”
Section: Discussionmentioning
confidence: 99%
“…In the San Antonio Heart Study, higher acculturation was associated with a significantly lower prevalence of obesity and diabetes among Mexican American women and men, independent of SES (18). Two other studies, based on data from the National Health and Nutrition Examination Survey (6) and data from the Hispanic Health and Nutrition Examination Survey (19), showed that the prevalence of diabetes was greater among Mexican-Americans in the middle group of acculturation (19). Only one study of which we are aware reported that a higher level of acculturation (as measured by language and country of origin) was associated with higher diabetes prevalence in Mexican Hispanics, after adjustment for age and sex (20).…”
Section: Results -Of the 2299mentioning
confidence: 99%
“…Incidence and prevalence of diabetes mellitus in Mexican Americans were reported to be nearly three times higher than in the non‐Hispanic white population. Furthermore, the prevalence of diabetes mellitus increases in older age groups and becomes proportionately larger for Mexican Americans compared with non‐Hispanic whites 16,18 …”
Section: Discussionmentioning
confidence: 99%